Speed and quality of interbody fusion in porous bioceramic Al2O3 and polyetheretherketone cages for anterior cervical discectomy and fusion: a comparative study - Kostysyn, Roman; Ryska, Pavel; Jandura, Jiri; Selke-Krulichova, Iva; Poczos, Pavel; Hosszu, Tomas; Cesak, Tomas (Journal of orthopaedic surgery and research, 2023)
BACKGROUND: The objective of this prospective randomized monocentric study is to compare the speed and quality of interbody fusion of implanted porous Al2O3 (aluminium oxide) cages with PEEK (polyetheretherketone) cages in ACDF (anterior cervical discectomy and fusion). MATERIALS AND METHODS: A total of 111 patients were enrolled in the study, which was carried out between 2015 and 2021. The 18-month follow-up (FU) was completed in 68 patients with an Al2O3 cage and 35 patients with a PEEK cage in one-level ACDF. Initially, the first evidence (initialization) of fusion was evaluated on computed tomography. Subsequently, interbody fusion was evaluated according to the fusion quality scale, fusion rate and incidence of subsidence. RESULTS: Signs of incipient fusion at 3 months were detected in 22% of cases with the Al2O3 cage and 37.1% with the PEEK cage. At 12-month FU, the fusion rate was 88.2% for Al2O3 and 97.1% for PEEK cages, and at the final FU at 18 months, 92.6% and 100%, respectively. The incidence of subsidence was observed to be 11.8% and 22.9% of cases with Al2O3 and PEEK cages, respectively. CONCLUSIONS: Porous Al2O3 cages demonstrated a lower speed and quality of fusion in comparison with PEEK cages. However, the fusion rate of Al2O3 cages was within the range of published results for various cages. The incidence of subsidence of Al2O3 cages was lower compared to published results. We consider the porous Al2O3 cage as safe for a stand-alone disc replacement in ACDF.
Keywords: poréznost; oxid hlinitý; polyethylenglykoly; Porosity; Ketones; Fusion rate; Prospective Studies; Quality of fusion; Non-union; Al2O3; Aluminum Oxide; Polyethylene Glycols; diskektomie; lidé; Subsidence; Humans; Diskectomy; PEEK; ketony; prospektivní studie